Implementasi Kebijakan Tentang Pengendalian dan Pengawasan Minuman Beralkohol di Minahasa Selatan (Studi Desa Kumelembuai, Kecamatan Kumelembuai) - Pangkey, Itje; Langkai, Hariandi J; Mokat, Jetty H. E (Academy of Education Journal, 2024)
This research aims to find out the process of supervision of alcoholic beverages in Kumelembuai Village, Kumelembuai District, South Minahasa Regency using a qualitative approach, with data collection techniques namely: observation, interviews and documentation. The data sources in this research are: Legal apparatus, local government, sellers of alcoholic beverages in Kumelembuai Village. The results showed that: (1) Lack of Supervision from the Government, 2) the seller does not have a license in the sale of alcoholic beverages. 4) Sellers lack knowledge about policies governing alcoholic beverages. 5) Sanctioning measures are only in the form of appeals to sellers of alcoholic beverages. For this reason, it is recommended that 1) Increase supervision regularly and periodically, not just on certain days or during holidays. 2) The government must also socialize information about making a Trade Business License (SIUP) 3) The government must apply strict and consistent sanctions against violations of the sale of alcoholic beverages.